Alpha-1 antitrypsin reduces inflammation and vasculopathy in mice with oxygen-induced retinopathy - Varaporn Suphapimol; Yu-Han Liu; Sandro Prato; Alexander Karnowski; Charles Hardy; Adriana Baz Morelli; Abhirup Jayasimhan; Devy Deliyanti; Jennifer L. Wilkinson-Berka (Journal of Inflammation)
Abstract Background Damage to the retinal vasculature is a major cause of vision loss and is influenced by a pro-inflammatory environment within retinal tissue. Alpha-1 antitrypsin (AAT) is a potent inhibitor of serine proteases and has anti-inflammatory properties. We hypothesised that AAT could reduce inflammation and vasculopathy in neovascular retinopathies including oxygen-induced retinopathy (OIR). Methods Litters of C57BL/6J mice were randomised to develop OIR by exposure to high oxygen between postnatal days 7 to 12 resulting in vaso-obliteration (phase I OIR), and then room air from postnatal days 12 to 18 resulting in neovascularisation (phase II OIR). Control mice were exposed to room air. Separate cohorts of mice were administered control vehicle or human AAT (120 mg/kg) by intraperitoneal injection every second day in phase I or phase II OIR. Results In phase I OIR, plasma levels of AAT were reduced compared to room air controls, and AAT treatment reduced vaso-obliteration. In phase II OIR, AAT treatment influenced inflammation by reducing the density of ionised calcium binding adaptor protein 1 + cells (microglia/macrophages) and modulating their cell process length and reducing mRNA levels of tumour necrosis factor and monocyte chemoattractant protein-1, but not interleukin-1b and interleukin-6 in retina. Furthermore, AAT treatment reduced retinal neovascularisation, gliosis, vascular endothelial growth factor mRNA and protein expression, and vascular leakage, compared to OIR controls. Conclusions This research demonstrates the vasculo-protective actions of AAT, and thereby the potential of AAT as a therapeutic option for neovascular retinopathies.